Anwar Ibrahim's Political Thoughts on Civil Society and Its Relevance to Politics in Malaysia - Anisma Zulfiani (International Journal on Social Science, Economics and Art, 2019)
The study covers internal, external background, development of thought, things that are noticed and under-noticed, strengths and weaknesses of the figure's thinking, as well as his contributions to his time, and the future. The study of the study of figures becomes so important in every age. That is why so many studies have been conducted by scholars on great figures throughout history. One of the figures who lives in the present era who has a name in the international world and gives tremendous influence to the people with his thoughts is Anwar Ibrahim a Muslim figure from Malaysia. This research aims to explore Anwar Ibrahim's thoughts on the concept of Madani society, the development of civil society and the relevance of civil society to politics in Malaysia. The method used is Library research with descriptive analysis form with qualitative approach. Hopefully this paper can add to the treasures of science about the study of figures, especially political science.